Modeling school choice: A comparison of public, private-independent, private-religious and home-schooled students - Belfield, Clive R. (Education Policy Analysis Archives, 2004)
U.S. students now have four choices of schooling:public schooling, private–religious schooling, private–independent schooling, and home-schooling. Of these, home-schooling is the most novel: since legalization across the states in the last few decades, it has grown in importance and legitimacy as an alternative choice. Thus, it is now possible to investigate the motivation for home-schooling, relative to the other schooling options. Here, we use two recentlarge-scale datasets to assess the school enrollment decision: the first is the National Household Expenditure Survey (1999), and the second is micro-data on SAT test-takers in 2001. We find that, generally, families with home-schoolers have similar characteristics to those with children at other types of school, but mother’s characteristics – specifically, her employment status – have a strong influence on the decision to home-school. Plausibly, religious belief has an important influence on the schooling decision, not only for Catholic students, but also those of other faiths.